The power of place : authentic learning through place-based education - Vander Ark, Tom, 1959-; Liebtag, Emily; McClennen, Nate (ASCD, 2020)
"The book offers a comprehensive and compelling case for place-based education and making communities the locus of learning for students of all ages and backgrounds"--